Multidimensionality and Renegotiation: Evidence from Transport-Sector Public-Private-Partnership Transactions in Latin America - Estache, Antonio; Guasch, Jose-Luis; Iimi, Atsushi; Trujillo, Lourdes (2012)
Multidimensional auctions are a natural, practical solution when governments pursue more than one objective in their public-private-partnership transactions. However, multi-criteria auctions seem difficult to implement and vulnerable to corruption and opportunistic behavior of both parties involved. Using data from road and railway concessions in Latin America, the paper examines the probability of renegotiation in connection with the selected award criteria. It shows that auctioneers tend to adopt the multidimensional format when the need for social considerations, such as alleviation of unemployment, is high. But more renegotiations would likely happen when the multidimensional format is used. Good governance, particularly regulatory quality and anti-corruption policies, can mitigate the renegotiation problem.